Analisis Penggunaan Media Sosial sebagai alat Promosi Ditinjau dari Instagram, Facebook, Tiktok dan Whatsapp - Wati, Sinta Kurnia; Pristiyono, Pristiyono; Gulo, Nurainun (Universitas Batanghari Jambi, 2024)
With social media now, the overall way consumers shop has changed, they purchase products online, from ordering to payment, they are done online. One way of electronic marketing and promotion is displaying advertisements on social media. The type of research used in this research is quantitative research. The sample taken in this research was 110 respondents. The data analysis method used in this research is variance based structural equation modeling where data processing uses the Partial Least Square (Smart-PLS) program. The research results found that social media and promotional variables had a significant effect on purchasing decisions.